Negative exploration for pyloric stenosis - Is it preventable? - Kenny Simon E; Losty Paul D; Craigie Ross J; Shariff Raheel; Mallappa Sreelakshmi; Mullassery Dhanya; Pilling David; Baillie Colin T (BMC, 2008)
Abstract Background The diagnosis of infantile hypertrophic pyloric stenosis (IHPS), although traditionally clinical, is now increasingly dependent on radiological corroboration. The rate of negative exploration in IHPS has been reported as 4%. The purpose of our study was to look at elements of supportive clinical evidence leading to positive diagnosis, and to review these with respect to misdiagnosed cases undergoing negative exploration. Methods All infants undergoing surgical exploration for IHPS between January 2000 and December 2004 were retrospectively analysed with regard to clinical symptoms, examination findings, investigations and operative findings. Results During the study period, 343 explorations were performed with a presumptive diagnosis of IHPS. Of these, 205 infants (60%) had a positive test feed, 269 (78%) had a positive ultrasound scan and 175 (55%) were alkalotic (pH ≥7.45 and/or base excess ≥2.5). The positive predictive value for an ultrasound (US) diagnosis was 99.1% for canal length ≥14 mm, and 98.7% for muscle thickness ≥4 mm. Four infants (1.1%) underwent a negative surgical exploration; Ultrasound was positive in 3, and negative in 1(who underwent surgery on the basis of a positive upper GI contrast). One US reported as positive had a muscle thickness <4 mm. Two false positive US were performed at peripheral hospitals. One infant had a false positive test feed following a positive ultrasound diagnosis. Two infants had negative test feeds. Conclusion A 1% rate of negative exploration in IHPS compares favourably with other studies. However potential causes of error were identified in all 4 cases. Confident diagnosis comprises a combination of positive test feed and an 'in house US' in an alkalotic infant. UGI contrast study should not be used in isolation to diagnose IHPS. If the test feed is negative, strict diagnostic measurements should be observed on US and the pyloric 'tumour' palpated on table under anaesthetic before exploration.